2016
DOI: 10.1289/ehp.1409111
|View full text |Cite
|
Sign up to set email alerts
|

Low-Concentration PM 2.5 and Mortality: Estimating Acute and Chronic Effects in a Population-Based Study

Abstract: BackgroundBoth short- and long-term exposures to fine particulate matter (≤ 2.5 μm; PM2.5) are associated with mortality. However, whether the associations exist at levels below the new U.S. Environmental Protection Agency (EPA) standards (12 μg/m3 of annual average PM2.5, 35 μg/m3 daily) is unclear. In addition, it is not clear whether results from previous time series studies (fit in larger cities) and cohort studies (fit in convenience samples) are generalizable.ObjectivesWe estimated the effects of low-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
183
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(202 citation statements)
references
References 48 publications
15
183
1
3
Order By: Relevance
“…The authors show that there is no threshold for ambient PM2.5 concentration below which it does not affect mortality. This finding is similar to other studies [4,5]. Using a household air pollution exposure index [6], it was found that exposure to Suspended Particulate Matter (atmospheric particulate matter with no limit size) is negatively correlated both with level of income and with level of education.…”
Section: Introductionsupporting
confidence: 90%
“…The authors show that there is no threshold for ambient PM2.5 concentration below which it does not affect mortality. This finding is similar to other studies [4,5]. Using a household air pollution exposure index [6], it was found that exposure to Suspended Particulate Matter (atmospheric particulate matter with no limit size) is negatively correlated both with level of income and with level of education.…”
Section: Introductionsupporting
confidence: 90%
“…Included studies showed that R 2 value of MEM was higher than those of the other three models in the same area [17,87,104,136]. Moreover, MAIAC algorithms, which led to a highly accurate of AOD, were mostly used in MEM, significantly improving the R 2 value of the model [7,35,83,120,135]. On the global scale, CTM has been proven to be efficient for the mechanism of completing the prediction from using partial AOD data by AOD component analysis [57]; (2) Adjusting factors: The number of these factors has increased due to the development of prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…In New England, Alexeeff et al [135] further employed the MEM model with [34,131] Kriging and land use regression to describe an epidemiological relationship between AOD and predicted PM 2.5 in 2003. The following year, Shi et al [120] used MEM to predict PM 2.5 using MODIS AOD data collected between 2003 and 2008, and they obtained consistent results (R 2 value = 0.890) for days with available AOD data and without available AOD data. This method was also successfully applied in studies on the relationship between low PM 2.5 exposure and mortality.…”
Section: Theory Background and Applicationmentioning
confidence: 96%
“…Removal efficiencies in the three size bins are then used to assign HVAC filters a single efficiency metric, which is the minimum efficiency reporting value (MERV), and is based on the minimum removal efficiency in each of the three bins. Although the vast majority of the epidemiological evidence of adverse health outcomes that are associated with airborne particulate matter to date has been linked to mass-based concentrations of PM 1 , PM 2.5 , and PM 10 [10][11][12][13][14][15][16][17][18][19][20], the ASHRAE Standard 52.2 test method does not explicitly evaluate particle removal efficiency for any of these mass-based measures.…”
Section: Introductionmentioning
confidence: 99%